PENGARUH PEMBELAJARAN BERBASIS PRAKTIKUM TERHADAP PEMAHAMAN SISWA PADA MATERI PERUBAHAN WUJUD BENDA - Dinnar Lambang Kinasih; Putri Dwi Hariyanto; Putri Wahyu Nurjanah; Syifa Nafiatus Sa’diyah; Yosita Purnawan Sari; Iwan Wicaksono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The research carried out had the aim of finding out students' understanding of the material on changes in the shape of objects using practicum. This research was carried out at Sdn Jenggawah 01 using 1 study group, namely class 5. This type of research was a paired sample t test with group pretest-posttest. The population in this study were 5th grade students at Sdn Jenggawah 01. One class of students consisted of 22 students. The instrument used in this research is a concept understanding test in the form of a 5-item multiple choice. This research makes an important contribution to the development of more effective learning methods in the context of natural science education, especially in teaching concepts that require visual understanding and direct practice such as changes in the shape of objects. The implications of these findings are also discussed in this article, including suggestions for curriculum development and teacher training to better utilize the potential of practicum-based learning in improving student understanding.